Senolytic Combination Treatment Is More Potent Than Single Drugs in Reducing Inflammatory and Senescence Burden in Cells from Painful Degenerating IVDs - Matthew Mannarino; Oliver Wu-Martinez; Kai Sheng; Li Li; Rodrigo Navarro-Ramirez; Peter Jarzem; Jean A. Ouellet; Hosni Cherif; Lisbet Haglund (Biomolecules, 2023)
Background: Low back pain is a global health problem directly related to intervertebral disc (IVD) degeneration. Senolytic drugs (RG-7112 and o-Vanillin) target and remove senescent cells from IVDs in vitro, improving tissue homeostasis. One drawback of using a single senolytic agent is the failure to target multiple senescent antiapoptotic pathways. This study aimed to determine if combining the two senolytic drugs, o-Vanillin and RG-7112, could more efficiently remove senescent cells and reduce the release of inflammatory factors and pain mediators in cells from degenerating human IVDs than either drug alone. Methods: Preliminary data evaluating multiple concentrations of o-Vanillin and RG-7112 led to the selection of four treatment groups. Monolayer and pellet cultures of cells from painful degenerate IVDs were exposed to TLR-2/6 agonist. They were then treated with the senolytics o-Vanillin and RG7112 alone or combined. p16ink4a, Ki-67, caspase-3, inflammatory mediators, and neuronal sprouting were assessed. Results: Compared to the single treatments, the combination of o-Vanillin and RG-7112 significantly reduced the amount of senescent IVD cells, proinflammatory cytokines, and neurotrophic factors. Moreover, both single and combination treatments significantly reduced neuronal sprouting in rat adrenal pheochromocytoma (PC-12 cells). Conclusions: Combining o-Vanillin and RG-7112 greatly enhanced the effect of either senolytic alone. Together, these results support the potential of senolytics as a promising treatment for IVD-related low back pain.